Theodore Harris, Charter and Ordinances of the City of San Antonio. Comprising All Ordinances of a General Character in Force August 7th, 1899, at 183-184, Concealed Weapons, § 1 (1899) - (:unkn) unknown (My University, 1899)
If any person, within the corporate limits of the city of San Antonio, shall carry on or about his or her person, saddle, or in his saddle bags, any pistol, dirk, dagger, sling shot, sword cane, spear, or knuckles made of any metal or any hard substance, bowie knife, or any other kind of knife manufactured or sold for purposes of offense or defense, he or she shall be punished by a fine of not less than twenty-five dollars ($25.00) nor more than two hundred dollars ($200.00).
Keywords: CARRY